The role of culture on workplace bullying: the comparison between the UK and South Korea - Seo, Yoojeong Nadine (2010)
This thesis begins by questioning the applicability of Western concepts and measures of workplace bullying to the Far East culture. Facing such an issue, the thesis aims to address the role of culture on workplace bullying by examining the emic and etic dimensions and developing an indigenous bullying scale. By emic was meant culturally specific dimension while by etic was meant culturally neutral dimension. Three studies were conducted which illustrated the emic and etic dimensions of workplace bullying. The first study was based on a questionnaire survey with 50 Korean and 43 UK employees and showed the extent of cultural differences in the employees’ concepts of and attitudes towards workplace bullying. Based upon these results, the qualitative part of the second study developed an indigenous bullying questionnaire (KBAQ: Korean Bullying Acts Questionnaire) through a repertory grid with 42 Korean participants. Then, the quantitative part of the study tested employees’ agreement of the KBAQ items being examples of bullying using a questionnaire survey with 76 Korean and 75 UK participants. Finally, the third study conducted a questionnaire survey utilising KBAQ and NAQ-R (Negative Acts Questionnaire-Revised). 193 Korean and 167 UK employees participated. The study highlighted cultural differences in the descriptive aspects of workplace bullying such as the prevalence rate, bully/perpetrator status, health outputs (e.g., job satisfaction and work-related burnout) and predictors (e.g., leadership style, role conflict, and interpersonal conflict). The results also evidenced the validity and reliability of KBAQ and revealed that KBAQ had a greater applicability for Korean employees and NAQ-R for UK employees. The consistent findings of cultural differences suggest the need for an indigenous approach in examining workplace bullying. This thesis makes a significant contribution to the literature on workplace bullying in the Far East and provides the ground for the advancement of the indigenous approach to workplace bullying research.